1997
DOI: 10.1111/j.1574-6976.1997.tb00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching: metal solubilization by microorganisms

Abstract: Bioleaching is a simple and effective technology for metal extraction from low‐grade ores and mineral concentrates. Metal recovery from sulfide minerals is based on the activity of chemolithotrophic bacteria, mainly Thiobacillus ferrooxidans and T. thiooxidans, which convert insoluble metal sulfides into soluble metal sulfates. Non‐sulfide ores and minerals can be treated by heterotrophic bacteria and by fungi. In these cases metal extraction is due to the production of organic acids and chelating and complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
244
1
23

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 731 publications
(317 citation statements)
references
References 45 publications
2
244
1
23
Order By: Relevance
“…Representatives of Bacillus have been reported to efficiently solubilize metals and thus contribute to metal leaching without any benefit to themselves [7] [33]. Only one other study found Bacillus from steelmaking waste sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representatives of Bacillus have been reported to efficiently solubilize metals and thus contribute to metal leaching without any benefit to themselves [7] [33]. Only one other study found Bacillus from steelmaking waste sources.…”
Section: Discussionmentioning
confidence: 99%
“…This biotechnological process is based on the ability of microorganisms to oxidize ferrous iron and/or reduce sulfur compounds [4]. The predominant metal-sulfide-dissolving bacteria that have been extensively used for the bioleaching of sulfide minerals with commercial interest are extremely acidophilic [5] [6] although heterotrophic bacteria can also contribute to metal leaching [7].…”
Section: Introductionmentioning
confidence: 99%
“…O uso de consórcios microbianos de bactérias autotróficas e bactérias ou fungos heterotróficos tem sido descrito na literatura. A produção de ácido lático, oxálico, cítrico e glucônico, por exemplo, auxiliam na solubilização direta do metal para a líxivia tanto pela troca direta de cátions quanto pela formação de complexos metálicos solúveis e quelatos [41].…”
Section: áCidos Orgânicosunclassified
“…광미의 위해도를 저감시키기 위해 고형화/안정화 (Desogus et al 2013)가 적용되고 있지만, 처리 후 광미에 대한 재이용 용도가 불분명하여 적치 또는 매립되고 있는 실정이다 (Bian et al 2012). Acidithiobacillus ferrooxidans와 같 은 철산화균을 이용하여 광미로부터 유용원소를 회수하기 위한 방안으로 활용되어온 생물학적 침출법 (bioleaching) 또한 광미의 위해도 저감기술의 하나로써 활용될 수 있다 (Bosecker 1997, Park et al 2014, Nguyen et al 2015.…”
Section: 서 론unclassified